ANALISIS DAMPAK EKONOMI KEBERADAAN DESA WISATA KEMANTREN TERHADAP PEREKONOMIAN MASYARAKAT LOKAL - Wulansari, Arta Dias; Yulistiyono, Herry (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to determine the respondent's perception of the economic impact of the existence of the Kemantren Tourism Village and to find out how big the economic impact of tourism activities in the Kemantren Tourism Village is on the economy of the local community. The method used is descriptive quantitative. The analytical method used is descriptive analysis and multiplier effect. The results showed that the perception of respondents stated the interpretation of "Strongly agree" and "Agree" to the statement regarding the economic impact of the existence of the Tourism Village Kemantren. And the economic impact of tourism activities includes a direct impact of Rp 182,285,708 per month, an indirect impact of IDR 111,452,222 per month, and a follow-up impact of Rp 28,400,218. Meanwhile, the total economic leakage is Rp 7,692,230,000 per month. The multiplier effect results show that the keynesian income multiplier value is 0.1, the type I income multiplier ratio is 1.6 and the type II income multiplier ratio is 1.8. With the keynesian income multiplier value of 0.1, it shows that the Tourism Village of Kemantren has a low economic impact on the economy of the local community.